Transparency in the Age of Uncertainty: A Comparative Analysis of the Government Communication Strategies of Iceland and the United States during the COVID-19 Pandemic - Reynir B. Ragnarsson 1997- (2021)
Since the beginning of the COVID-19 pandemic in January 2020 nearly all countries have adopted a coordinated public communication strategy to communicate health guidelines and information to their citizens. The aim of this thesis was to analyze and compare the communication strategies of Iceland and the United States from when the pandemic was beginning in February of 2020 to late May. The metrics which were used to analyze their respective strategies were transparency, clarity, and consistency. The secondary goal was to see if speakers framed risk management as more of an individual responsibility or civic duty by applying the cultural theory of risk. The results showed that while speakers in both countries were mostly transparent, concise, and clear in early briefings, as time went on, the messages being communicated in the United States became less transparent, less clear, and less concise. In Iceland, there were fewer such instances and speakers remained as transparent, clear, and concise in the beginning of the analysis as in the end. However, in both countries most speakers framed risk management as a collective responsibility that each citizen had rather than an individual choice or something that had to be adhered to the threat of punishment.